Autonomous Manufacturing of Composite Parts by a Multi-Robot System - Schuster, Alfons; Kupke, Michael; Larsen, Lars (Procedia manufacturing, 2017)
This work considers an autonomous multi-robot pick-and-place process for the manufacturing of aerospace structures, which consists of the steps picking, transfer, dropping and post-drop treatment. Autonomous production is achieved by combining computer vision assisted gripping, automated transfer path generation and generic process execution in one system. Test scenario is an airplane skin demonstrator made of tailored carbon fiber multiaxial fabrics that are placed in a half-shell shaped jig of approximately 4 m in diameter by two cooperating robots mounted on a common linear axis.